Optimasi Resiliensi Rantai Pasok Lokal melalui Model FRAC-R (Analisis Koefisien Kompleksitas dan Mitigasi Risiko Agilitas dan Kolaborasi) - Suwaryo Nugroho; Muhamad Ali Pahmi (Journal Industrial Manufacturing, 2026)
CV. Alden Nature is an MSME that rents outdoor equipment for outdoor activities for customers who want to do activities outside the home, whether at campsites, open nature or mountainous areas. The demand for outdoor equipment rentals has increased from year to year thanks to good service and customer trust. However, uncertain physical and weather conditions and the high number of natural disasters and VUCA conditions suppress the company's ability to develop its business. The FRAC_R model is a model that can improve the ability of the supply chain to be more resilient amid uncertainty. The implementation of the FRAC_R model in Alden Nature MSMEs can improve the resilience of the supply chain through improvement strategies for dimensions and indicators with relatively low capabilities and accelerate the TTR (Time To Recover). The results of the analysis and calculations obtained that the supply chain resilience capability index of 2.7 is included in the medium category with a medium level of risk and complexity of 0.8, can improve TTR 29-39% from the TTR baseline.Key Words: Supply Chain Resilience, Time to Recover, FRAC_R